Glomerulonephritiden – nicht nur für den Nephrologen wichtig - Stahl, Rolf A. K. (DMW - Deutsche Medizinische Wochenschrift, 2020)
Chronic kidney disease (CKD) is an increasing health problem in all societies. The role of diabetes mellitus and hypertension in CKD is well established in the medical community. This is not necessarily the case for the various forms of glomerulonephitis (GN). The single entities of GN are rare diseases. In total, glomerulonephritis, however, is accountable for about 20 % of all patients which reach end stage renal disease (ESRD). GN therefore plays an important clinical role. Since many forms of GN have only sparse clinical symptoms at the beginning of the disease and the treatment is only effective in early stages, it is important for patients’ outcome to make an early diagnosis. In case of any – even small – changes in the urine of patients the diagnoses of GN should be considered. It is the purpose of this article to describe the clinical significance and the road to the diagnosis of the most frequent forms of GN to allow an early start of therapy in order to prevent the development of ESRD.
Keywords: Glomerulonephritiden; Nierenerkrankung; chronische Niereninsuffizienz